Hadislerin Anlaşılmasında Belagat İlminin Önemi - Köktaş, Yavuz (Dinî araştırmalar, 2002)
Ilm al-balagah is known amongst the necessary science to understand the Qur'an and the Sunnah. ıt's the fact that ilm al-balagah investigates the literay direction of the language. But in this study we will examine the relationship of ilm al-balagah with meaning (anlam) or intention (murad). In another expression) we will study to show with examples how ilm al-balagah gives an opportunity to expose the meaning or the intention presenting a text. The understanding of hadiths is primarily the question of the language. A languiage is a social phenomena and necessary to be known in all aspects. This science also gives an opportunity in exposing the intention of the Prophet namely, the meaning in hadith. Indeed ilm al-balagah is an attractive one by considering the situatins of address (al-hitab) and addressed one (al-muhatab) in understanding what has been meant in a hadith. Both ilm alma- 'ani-ilm al-bedi' and ilm al-bayan give us an outlet to understand a hadith apart from its literal meanings